IMPLEMENTASI KONSEP KEADILAN RESTORATIF DALAM PERKARA ANAK YANG BERKONFLIK DENGAN HUKUM DI KEPOLISIAN RESORT KOTA BESAR MAKASSAR - Muh Rijal; Sufirman Rahman; Baharuddin Baharu (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
The application of restorative justice at the Makassar Police Station has been carried out, both before and after promulgation and the enactment of the Republic of Indonesia Law Number 11 Year 2012 concerning the Child Criminal Justice System, this is evidenced by many child cases resolved by deliberation and not yet reached the stage of investigation.